Single-legged Hop Tests as Predictors of Self-reported Knee Function After Anterior Cruciate Ligament Reconstruction: The Delaware-Oslo ACL Cohort Study - Logerstedt, David (2012)
BACKGROUND: Single-legged hop tests are commonly used functional performance measures that can capture limb asymmetries in patients after anterior cruciate ligament (ACL) reconstruction. Hop tests hold potential as predictive factors of self-reported knee function in individuals after ACL reconstruction. HYPOTHESIS: Single-legged hop tests conducted preoperatively would not and 6 months after ACL reconstruction would predict self-reported knee function (International Knee Documentation Committee [IKDC] 2000) 1 year after ACL reconstruction. STUDY DESIGN: Cohort study (prognosis); Level of evidence, 2. METHODS: One hundred twenty patients who were treated with ACL reconstruction performed 4 single-legged hop tests preoperatively and 6 months after ACL reconstruction. Self-reported knee function within normal ranges was defined as IKDC 2000 scores greater than or equal to the age- and sex-specific normative 15th percentile score 1 year after surgery. Logistic regression analyses were performed to identify predictors of self-reported knee function within normal ranges. The area under the curve (AUC) from receiver operating characteristic curves was used as a measure of discriminative accuracy. RESULTS: Eighty-five patients completed single-legged hop tests 6 months after surgery and the 1-year follow-up with 68 patients classified as having self-reported knee function within normal ranges 1 year after reconstruction. The crossover hop and 6-m timed hop limb symmetry index (LSI) 6 months after ACL reconstruction were the strongest individual predictors of self-reported knee function (odds ratio, 1.09 and 1.10) and the only 2 tests in which the confidence intervals of the discriminatory accuracy (AUC) were above 0.5 (AUC = 0.68). Patients with knee function below normal ranges were over 5 times more likely of having a 6-m timed hop LSI lower than the 88% cutoff than those with knee function within normal ranges. Patients with knee function within normal ranges were 4 times more likely to have a crossover hop LSI greater than the 95% cutoff than those with knee function below normal ranges. No preoperative single-legged hop test predicted self-reported knee function within normal ranges 1 year after ACL reconstruction (all P > .353). CONCLUSION: Single-legged hop tests conducted 6 months after ACL reconstruction can predict the likelihood of successful and unsuccessful outcome 1 year after ACL reconstruction. Patients demonstrating less than the 88% cutoff score on the 6-m timed hop test at 6 months may benefit from targeted training to improve limb symmetry in an attempt to normalize function. Patients with minimal side-to-side differences on the crossover hop test at 6 months possibly will have good knee function at 1 year if they continue with their current training regimen. Preoperative single-legged hop tests are not able to predict postoperative outcomes.